Discovery of Novel Human Constitutive Androstane Receptor Agonists with the Imidazo[1,2-a]pyridine Structure - Mejdrová, Ivana; Dušek, Jan; Škach, Kryštof; Stefela, Alžbeta; Skoda, Josef; Chalupský, Karel; Dohnalová, Klára; Pavkova, Ivona; Kronenberger, Thales; Rashidian, Azam; Smutná, Lucie; Duchoslav, Vojtěch; et al. (Journal of medicinal chemistry, 2023)
The nuclear constitutive androstane receptor (CAR, NR1I3) plays significant roles in many hepatic functions, such as fatty acid oxidation, biotransformation, liver regeneration, as well as clearance of steroid hormones, cholesterol, and bilirubin. CAR has been proposed as a hypothetical target receptor for metabolic or liver disease therapy. Currently known prototype high-affinity human CAR agonists such as CITCO (6-(4-chlorophenyl)imidazo[2,1-b][1,3]thiazole-5-carbaldehyde-O-(3,4-dichlorobenzyl)oxime) have limited selectivity, activating the pregnane X receptor (PXR) receptor, a related receptor of the NR1I subfamily. We have discovered several derivatives of 3-(1H-1,2,3-triazol-4-yl)imidazo[1,2-a]pyridine that directly activate human CAR in nanomolar concentrations. While compound 39 regulates CAR target genes in humanized CAR mice as well as human hepatocytes, it does not activate other nuclear receptors and is nontoxic in cellular and genotoxic assays as well as in rodent toxicity studies. Our findings concerning potent human CAR agonists with in vivo activity reinforce the role of CAR as a possible therapeutic target.
Keywords: konstitutivní androstanový receptor; hepatocyty; Hepatocytes; Animals; pyridiny; Humans; lidé; zvířata; Mice; Receptors, Steroid; Constitutive Androstane Receptor; Receptors, Cytoplasmic and Nuclear; steroidní receptory; Pyridines; receptory cytoplazmatické a nukleární; myši